Modernisasi Penafsiran Al-Quran Dalam Tafsir Al-Azhar Karya Buya Hamka - Umi Wasilatul Firdausiyah (Jurnal Ulunnuha, 2021)
The Discourse of this research, focuses on the modernization of the interpretation of the Qur’an from the perspective of the Tafsir al-Azhar by Buya Hamka. The purpose of the study, to reveal the impact of modernization on the realm of interpretation of the Qur’an and to determine the development of the interpretation of the Qur’an by looking at the extent to which the Tafsir al-Azhar can be categorized in the realm of modernization of the interpretation of the Qur’an. This research is in the form of qualitative  research, the type of library research is assisted by data analysis in the form of descriptive analysis, and to determine the significance of Tafsir al-Azhar, the author uses the interpretation theory of the interpretation of the Qur’an Nasr Hamid Abu Zayd, in order to be able to see the representation of the text of Tafsir al-Azhar has any reference to modernization or not, and is equipped with theorical triangulation as a test of the validity of the data. The results of the study state that the existence of Tafsir al-Azhar is representation of modern interpretation because of ist efforts to contextualize the text with events that are currently happening, driven by the emergence of modernization, and modernization of the interpretation of the Qur’an is also an implementation of the involvement of interpretation with modern problems, as the interpretation of Buya Hamka in the Tafsir al-Azhar which discusses a lot of modern problems. This is an attempt by the mufasir to maintain the Qur’an which should indeed be salih likulli zaman wa makan.